2020
DOI: 10.1016/j.heliyon.2020.e04052
|View full text |Cite
|
Sign up to set email alerts
|

Elementary students’ perceptions of 3Dmetric: A cross-sectional study

Abstract: Rapid changes in the 21st century demand the use of technology in learning geometry in elementary schools. One such technology is augmented reality (AR). 3Dmetric (3D and Geometric) is a geometry learning medium on ARbased 3D space material. Students' perceptions, which refer to their interpretation, are a key factor in studying the changes in their interpretations of a particular phenomenon. The purpose of the current study was to investigate the perceptions of elementary school students after using 3Dmetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…It is indicated that if the individual has a good view of something or other people, it will also benefit him/herself. Perception can also be considered an individual's interpretation of something (Amir et al, 2020). This opinion is in line with that expressed by Arifin, that perception is a process of giving meaning, interpretation of stimuli and sensations received by individuals, and is strongly influenced by internal and external factors of each individual (Hadi et al, 2017).…”
Section: Student Perceptionsupporting
confidence: 56%
“…It is indicated that if the individual has a good view of something or other people, it will also benefit him/herself. Perception can also be considered an individual's interpretation of something (Amir et al, 2020). This opinion is in line with that expressed by Arifin, that perception is a process of giving meaning, interpretation of stimuli and sensations received by individuals, and is strongly influenced by internal and external factors of each individual (Hadi et al, 2017).…”
Section: Student Perceptionsupporting
confidence: 56%
“…The homepage feature is used to show student profiles and progress in courses. The mobile features that can record student achievement progress will cause students to have a positive perception of learning and learning awareness [21], [22]. In addition, the progress of the achievements recorded every time will form an initial self-evaluation and independently to always learn to improve and learn to prepare to be better prepared for the next lesson [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated that if the individual has a good view of something or other people, it will also benefit him/herself. Perception can also be considered an individual's interpretation of something (Amir et al, 2020). Perception is conveyed in the form of idea or action, human idea based on their experience.…”
Section: Students' Perspectivementioning
confidence: 99%